2000
DOI: 10.1128/aac.44.5.1359-1361.2000
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a Salmonella enterica Serovar Typhimurium DT104-Like Antibiotic Resistance Gene Cluster Including the floR Gene in S. enterica Serovar Agona

Abstract: Recently a chromosomal locus possibly specific for Salmonella enterica serovar Typhimurium DT104 has been reported that contains a multiple antibiotic resistance gene cluster. Evidence is provided that Salmonella enterica serovar Agona strains isolated from poultry harbor a similar gene cluster including the newly described floR gene, conferring cross-resistance to chloramphenicol and florfenicol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 13 publications
4
85
0
Order By: Relevance
“…Thus irrespective of source and country of origin the investigated R-type ACSSuSpT strains contained the same inserted gene cassettes. In addition to these findings, other investigations [9,10] however showed that the chromosomally located antibiotic resistance genes also occur in other phage-types rather than DT104 and more interestingly also in another Salmonella serovar, namely Salmonella Agona. This could be indicative of horizontal transfer of the antibiotic resistance gene cluster, perhaps phage-mediated.…”
Section: Horizontal Gene Transfer Versus Clonal Spreadmentioning
confidence: 74%
“…Thus irrespective of source and country of origin the investigated R-type ACSSuSpT strains contained the same inserted gene cassettes. In addition to these findings, other investigations [9,10] however showed that the chromosomally located antibiotic resistance genes also occur in other phage-types rather than DT104 and more interestingly also in another Salmonella serovar, namely Salmonella Agona. This could be indicative of horizontal transfer of the antibiotic resistance gene cluster, perhaps phage-mediated.…”
Section: Horizontal Gene Transfer Versus Clonal Spreadmentioning
confidence: 74%
“…These multidrug-resistant serovar Agona strains were isolated from poultry in Belgium during the 1992-1997 period [24], but have not yet been reported in other countries. Besides this observation, the DT104 antibiotic resistance gene cluster has also been shown to occur in phage type DT120 of serovar Typhimurium [18]. A possible mechanism by which this antibiotic resistance gene cluster may be horizontally transferred is phage-mediated transfer.…”
Section: Clonal Spread and Horizontal Transfer Of The Antibiotic Resimentioning
confidence: 81%
“…Multiplex PCR based on the surrounding genes of the antibiotic resistance gene cluster has also been proposed for the identification of S. enterica Typhimurium DT104 strains [5,12,26]. In the light of evidence of horizontal transfer of the DT104 antibiotic resistance gene cluster to other Typhimurium phage types or other S. enterica serovars [18], these methods appear to be no longer suitable for the specific detection of multidrug-resistant S. enterica Typhimurium DT104. Let us also mention the recently described occurrence of florfenicol resistance encoded by the floR gene on conjugative plasmids or on the chromosome of Escherichia coli isolated from cattle and poultry [17,25,53].…”
Section: Molecular Identification and Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efflux systems which confer either only chloramphenicol resistance or combined resistance to chloramphenicol and florfenicol have also been described [2,3,8,17,18,32,77]. Permeability barriers and multidrug transporters only play a role in certain gram-negative bacteria [44,48].…”
Section: Resistance To Chloramphenicol and Florfenicolmentioning
confidence: 99%